Sosialisasi Pentingnya Integritas Struktur Kapal Kayu Dalam Penjaminan Keselamatan : Masyakarat Sasaran Kelompok Pengrajin Kapal Kayu di Takalar - Hamzah Hamzah Hamzah; Ganding Sitepu '; Andi Ardianti .; Mansyur Hasbullah .; Rosmani .; M. Rizal Firmansyah .; Wahyuddin .; Muhammad Akbar Asis . (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
The operational activities of wooden ships are classified as very high so that the production of wooden boats still survives today, one of the groups of craftsmen in Takalar Regency is the "TORANI" group which specializes in producing wooden ships of 10 GT to 30 GT. High wooden ship operation activity, must always be improved quality in ensuring the safety of the ship improve the quality of ships in ensuring ship safety, the problems currently faced by partners are ship structure damage due to understanding of connection techniques, selection of ship construction dimensions and the use of bolts and pegs are not yet weak because the construction method is still based on experience. Based on observations in the field, it can be seen that there are many weaknesses made by craftsmen or builders in the connection of structures and also the selection or determination of the dimensions of the structure for example the placement of supports and beams are not fully in accordance with the global load and local loads of the ship structure, another weakness is the selection of the type of connection and the determination of dimensions not in accordance with existing regulations. To be able to provide an understanding, craftsmen need to be given socialization with the target craftsmen being able to recognize the importance of construction strength in ensuring ship safety, being able to use techniques for connecting construction components that meet the criteria and standards, selecting dimensions that match the criteria and standards and the correct bolts and pegs in component connection. wooden boat construction. The results obtained that the level of understanding and skills of the wooden ship craftsmen who received this training was very good. This is evidenced by the ability of the craftsmen to be able to apply construction connection methods